Islamic Law in the Digital Era: Artificial Intelligence as A Revolutionary Legal Tool in The 21st Century - Edo Rahman, Muhammad; Syahriani, Fadilla; Jampa, Wilibaldus (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
artificial intelligence (AI) as a transformative force in various sectors, including the legal domain. This research uses a qualitative approach to explore the intersection between Islamic law and AI, and how AI serves as a revolutionary tool that reshapes the practice and interpretation of Sharia in the digital age. Through qualitative methods such as in-depth interviews with Islamic legal experts, content analysis of legal literature, as well as case studies of AI applications in the context of Islamic law, this research explores how AI can improve legal reasoning, streamline judicial processes, and ensure more accurate and consistent legal outcomes in Islamic jurisprudence. The research offers a comprehensive analysis of the opportunities and challenges presented by AI in the context of Islamic legal practice, and proposes a balanced approach in utilising the technology while upholding the integrity of Sharia. The findings contribute to a deeper understanding of the role of AI in the modernisation of Islamic law, paving the way towards a future where technology and tradition can coexist harmoniously.